Cities, business, and the politics of urban violence in Latin America - Moncada, Eduardo, 1977- (Stanford University Press, 2016)
This text analyzes and explains the ways in which major developing world cities respond to the challenge of urban violence. The study shows how the political projects that cities launch to confront urban violence are shaped by the interaction between urban political economies and patterns of armed territorial control. It introduces business as a pivotal actor in the politics of urban violence, and argues that how business is organized within cities and its linkages to local governments impacts whether or not business supports or subverts state efforts to stem and prevent urban violence. A focus on city mayors finds that the degree to which politicians rely upon clientelism to secure and maintain power influences whether they favour responses to violence that perpetuate or weaken local political exclusion.